(untitled) (Bangladesh Journal of Zoology, 2010)
A total of 24 water samples were collected from March 2005 to February 2006 from a permanent station of Gulshan lake. The eggs and larva of four types of helminth parasites were identified; two were helminth eggs of Ascaris lumbricoides and Trichuris trichiura and two were helminth larva (rhabditiform larvae) of Strongyloides stercoralis and hookworm. The eggs and larvae of A. lumbricoides was found in all samples and it was numerically dominant over the eggs and larvae of other parasites. Its intensity was the highest (33.50) in winter and lowest (12.75) in rainy season. In case of T. trichiura, the prevalence was 25% with highest egg count in January. The prevalence and intensity of T. trichiura were the highest in winter and lowest in rainy season. The prevalence of the helminth larva was the highest in summer (37.5% for both) and lowest in rainy season (12.5% for both). Faecal coliform count (7.38 and 7.2 log10 cfu/L) also showed similar trends. All the physico-chemical parameters of water showed highest value in the summer. Among them conductivity and pH were the lowest in rainy, and salinity, DO, TDS were the lowest in the winter season. A positive correlation between S. stercoralis and hookworm larvae indicates that both of them were abundant at the same time in the water samples. Ascaris lumbricoides and T. trichiura eggs were also significantly correlated. The abundance of nematode larvae was inversely correlated with TDS. The present study suggests that the occurrence of different helminth eggs and larvae in the lake water are beyond the acceptable limit recommended by WHO. Bangladesh J. Zool. 38(1): 31-39, 2010